Reactions of 1-Alkyl-3-phenylbenzimidazolium Salts with Ag2O: The Formation of a Ring-Opening Formamide Derivative and a Ag Complex with an N-heterocyclic Carbene Ligand - Satoshi Sakaguchi; Takashi Higashino; Yudai Tasaki; Ryo Ichihara; Tatsuo Yajima (Inorganics)
This study investigated the reactions of 1-alkyl-3-phenylbenzimidazolium salts with Ag2O. It was found that the selectivity of the reaction products was influenced by the N-alkyl substituent on the azolium ring. For example, treating 1-methyl-3-phenylbenzimidazolium iodide (2) with Ag2O for 24 h produced the ring-opening formamide derivative N-[2-(phenylamino)phenyl]-N-methylformamide (2b) in an 85% yield. In contrast, the reaction of 1-benzyl-3-phenylbenzimidazolium chloride (3) with Ag2O under the same conditions yielded the corresponding N-heterocyclic carbene (NHC)–Ag complex (1-benzyl-3-phenylbenzimidazol-2-ylidene) silver(I) chloride (3a) in an 86% yield. Furthermore, the corresponding monodentate NHC–Au complex 2c could be synthesized by allowing 2 to react with AuCl(SMe2) in the presence of Ag2O.